Screening for Postpartum Depression Risk Using Edinburgh Postnatal Depression Scale (EPDS) In Postpartum Mothers - Anggarani, Ni Luh Ayu Sri; Dwina Mastryagung, Gusti Ayu; Sri Ariani, Ni Komang (Care : Jurnal Ilmiah Ilmu Kesehatan, 2024)
Postpartum depression seems to be one of the prior causes of stress and anxiety for women worldwide during the current COVID-19 pandemic. This percentage is quite high in Asian countries, ranging from 26 to 85%, and 50 to 70% in Indonesia. This research aims to describe the prevalence of postpartum depression risk in postpartum mothers using EPDS in Bali Mandara Public Hospital, Bali Province. With a sample size of 75 postpartum mothers, the design of this descriptive study was the cross-sectional approach of seventh to tenth-day postpartum mothers from November to December 2022. The sampling technique involved consecutive sampling. The research instrument is the EPDS questionnaire. Approximately 41.3% of postpartum mothers who gave birth in Bali Mandara Public Hospital had a high risk of experiencing postpartum depression. The respondents are 16-20 years old, have an elementary education level, work as entrepreneurs, have middle to low economic status, and have multiparity. The majority of postpartum mothers are at high risk of experiencing postpartum depression, which is why early detection is critical and must be established as the new operational standard in perinatal health services.